Breaking through the selectivity-permeability tradeoff using nano zeolite-Y for micellar enhanced ultrafiltration dye rejection application - Nidal Hilal (Separation and Purification Technology, 2020)
Membrane performance is a region of growing research interest, where new functional nanomaterials are continually sought. In this study, nano zeolite type Y was prepared through a unique ball milling process. The produced zeolite has a high surface area, and abundant flow channels with a well-defined pore structure facilitating water passage, but at the same time restricting the passage of contaminants through the molecular sieving effect. Polysulfone (PSf) membranes were prepared through phase inversion with nano-Y loadings from 0.2 to 1.5 wt. %. Membranes were characterized for their structure, morphology, thermal stability and porosity. The developed membranes were tested for micellar enhanced ultrafiltration (MEUF) cationic dye rejections. The addition of nano-Y zeolite affected both the flux and dye rejection of the membranes. Optimum performance was obtained at 0.4 wt. % nano-Y loading, giving a rejection of 99.5% and a corresponding flux of 105 L.m-2.h-1. The static contact angle measurements indicate that membrane hydrophilicity increased with progressive nano-Y additions until 0.4 wt. %, after which the membrane showed no further change in hydrophilic character. The obtained effects of nano-Y addition on membrane performance was attributed to the well-connected 3-D microporous structure in which nano-Y zeolite provided preferential water pathways though nanoporous hydrophilic channels. Whereas, the high dye rejection was attributed to the fact that nano-Y zeolite is negatively charged and, as a result, provided resistance to the negatively charged micelles, and further restricted its passage through the microporous zeolite structure.